The contralateral effects of foam rolling on range of motion and muscle performance - Konrad, A.; Nakamura, M.; Warneke, K.; Donti, O.; Gabriel, A. (European Journal of Applied Physiology, 2023)
A single bout of foam rolling (FR) can acutely increase joint range of motion (ROM) without detrimental effects on subsequent muscle performance. Similarly, long-term FR training can increase ROM, while muscle performance seems to be unaffected. Although the acute and long-term effects of FR on the treated muscle are understood, the impact of FR on the contralateral side is not well known. Therefore, this scoping review aims to summarize the current evidence on the acute and long-term effect of FR on the ipsilateral limb on ROM and muscle performance (i.e., maximum force, rate of force development, jump height) for the contralateral (non-treated) limb. Potential explanatory mechanisms are also discussed. There is evidence that a single bout of FR on the ipsilateral limb increases ROM of the contralateral limb; however, evidence is limited for long-term effects. The most likely mechanism for contralateral ROM increases is a reduced perception of pain. With regard to isolated muscle contractions, no changes in muscle performance (i.e., maximum voluntary isometric contraction, maximum voluntary dynamic contraction) were found in the contralateral limb after a single bout of FR on the ipsilateral limb. Notably, only one study reported large impairments in rate of force development of the contralateral limb following FR on the ipsilateral leg, possibly due to decreased motor unit recruitment. Furthermore, to date there are only two studies examining the long-term FR training of the ipsilateral limb on performance (i.e., maximal strength and jump performance) which reported moderate improvements. Although, trivial to very large changes on a variety of parameters were found in this study, the functional and practical relevance of our findings should be interpreted with caution.